Редкие и новый для науки циклопы группы Diacyclops languidoides s.l. (Crustacea, Copepoda) - Монченко, В.И. (Вестник зоологии, 1980)
An illustrated description of D. cohabitatus sp. n. from two wells in Forecarpathian area in the Ukraine is given. It differs from D. languidoides s. 1. by reproductive isolation (live with D. languidoides clandestinus in both habitats), by equal length of two apical spines on P4, by divergence of this apical spines (30-50°), by index of innermost and outermost apical setae (1.25-1.58; on the average 1.4). Additional indices are: furca in female 4.9 (4.4-5.8), P4 distal joint 1.74 (1.66-1.96). Its inner apical spine is 76% (73-82) of joint length. D. languidoides cf. italianus and D. l. hypnicola are recorded for the first time in the Soviet Union.